Potential of Energy Integration in Mashreq and Neighboring Countries - World Bank (Washington, DC, 2012)
The objective of this study is to carry out a country-by-country analysis of the power and gas sector demand and supply picture in order to assess opportunities for regional energy integration in the Mashreq and neighboring countries, and to identify specific interconnection projects that may require support from the World Bank and other international financiers. The study is conducted in the context of the World Bank Arab World Initiative. Although the present study focuses on Mashreq countries, issues of regional integration are intertwined among various Middle East and North Africa (MENA) sub-regions, and Turkey with eventual integration with Europe, so Mashreq is not considered in isolation. There are two other parallel efforts to examine the energy integration potential in the Maghreb and the Gulf Cooperation Council (GCC) countries. In addition, the World Bank and its partners are implementing a major solar power initiative with support from the Clean Technology Fund (CTF) to assist the MENA countries with development of large scale concentrated solar power (CSP) electricity generation capabilities for their own use or for export to other countries. Large scale development of solar power is expected to support and facilitate regional integration among MENA countries and with Europe as well.